Serosurvey for Brucella spp. and Coxiella burnetii in animals on Caribbean islands. Issue 1 (14th November 2019) - Johnson, Jason W.; Lucas, Helene; King, Sharon; Caron, Tyler; Wang, Chengming; Kelly, Patrick J.
Abstract: To determine the prevalence of antibodies to Brucella melitensis, Brucella abortus and Coxiella burnetii in animals on Caribbean islands we obtained sera from convenience samples of cattle (C), sheep (S), goats (G) and cats (F) from Dominica (C, S, G), Grenada (C, S, G), Montserrat (C, S, G), Puerto Rico (C), Nevis (C, S, G), St Kitts (C, S, G, F) and St Lucia (C, G). The sera were tested for antibodies against the Brucella spp. using commercial ELISA kits. Some sera were also tested at 1/80 for antibodies to C. burnetii using an indirect fluorescent antibody test. Positive sera were also tested at 1/640. None of 599 cattle, 462 sheep or 434 goats were positive in the Brucella ELISAs. None of 230 cattle had antibodies against C. burnetii, but one of 299 sheep was positive at 1/80 (Dominica – 1/54, 2%, 95% CI (0%–5.6%)), as were two of 314 goats, at 1/80 (Grenada – 1/53, 2%, 95% CI (0%–7.5%)) and 1/640 (St Kitts − 1/18, 5.6%, 95% CI (0%–16.7%)), and one of 34 cats, at 1/80 (St Kitts − 1/34; 3%, 95% CI (0%–8.8%)). Our data suggests that there is a very low prevalence or absence of B. melitensis and B. abortus on Caribbean islands. Coxiella burnetii, however, is present but it appears to be present on only some islands and then only at low levels. Overall, there appears to be a low threat to human and animal health from these organisms in the Caribbean. Abstract : A serosurvey of animals from Caribbean islands showed little evidence of exposure to Coxiella burnetii and Brucella spp., the agents of Q fever and brucellosis in animals and people, respectively. The findings indicate that there appears to be a low threat to human and animal health from these organisms in the region.